The Need for Ocular Protection for Health Care Workers During SARS-CoV-2 Outbreak and a Hypothesis for a Potential Personal Protective Equipment - Wang, Lixiang; Deng, Yingping (Frontiers in Public Health, 2020)
SARS-CoV-2 is a coronavirus with high infectivity and has caused dramatic pressure on health systems all over the world. Appropriate personal protection for medical staffs is critical. For ocular protection, there is ongoing debate and concern for potential ocular transmission of SARS-CoV-2. Ocular manifestations and positive detection of viral RNA in ocular samples were only reported in very small numbers of patients infected with SARS-CoV-2. However, health care workers need to face patients more closely and had higher risk of aerosol contamination. Thus, appropriate ocular protection for medical workers is still recommended by organizations such as WHO and American Academy of Ophthalmology. Although eye goggles provide excellent protection and are mandatory for medical practitioners with high risk of exposure, they are not practical for common clinical practice, because they can disturb vision due to extensive formation of water droplets and frequently cause moderate to severe discomfort after longtime wearing, which have been reported to interfere with working status. For the majority of medical workers who don’t deal with high risk patients, they are not advised to wear goggles in daily practice. However, they also face the risk of infection due to the presence of asymptomatic carriers. Especially in situations with high risk of ocular exposure, such as close physical examination, eye surgery, dental clinics and surgery, ocular protection may be needed. Griffithsin has been shown to directly bind to spike proteins and has anti-viral activity against a broad spectrum of viruses, including coronavirus. Griffithsin is found to inhibit the entry of SARS-CoV at relatively low concentration and is stable and non-toxic. SARS-CoV-2 and SARS-CoV share the same entry receptors and their spike proteins are similar in conformation. We hypothesize that contact lenses containing nanoparticles loaded with griffithsin may provide sufficient ocular protection for medical staffs without high risk of exposure during the outbreak period of SARS-CoV-2. If proven effective, griffithsin-loaded contact lens can be considered as a supplementary ocular protective equipment for medical workers who can tolerate well. The daily disposable contact lens should be applied as needed and refrain from extended wearing in order to reduce potential side effects.